2021
DOI: 10.1007/s11423-021-10057-w
|View full text |Cite
|
Sign up to set email alerts
|

The positivity principle: do positive instructors improve learning from video lectures?

Abstract: The positivity principle states that people learn better from instructors who display positive emotions rather than negative emotions. In two experiments, students viewed a short video lecture on a statistics topic in which an instructor stood next to a series of slides as she lectured and then they took either an immediate test (Experiment 1) or a delayed test (Experiment 2). In a between-subjects design, students saw an instructor who used her voice, body movement, gesture, facial expression, and eye gaze to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Noteworthy, this study's finding could have been attributed to the immediate posttest, which might not have effectively detected voice enthusiasm effects on learning outcomes (Wang et al, 2022). A delayed posttest may be more sensitive for discerning voice effects on learning performance concerning deep learning (Lawson et al, 2021b) and long-term knowledge acquisition (Davis et al, 2019).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Noteworthy, this study's finding could have been attributed to the immediate posttest, which might not have effectively detected voice enthusiasm effects on learning outcomes (Wang et al, 2022). A delayed posttest may be more sensitive for discerning voice effects on learning performance concerning deep learning (Lawson et al, 2021b) and long-term knowledge acquisition (Davis et al, 2019).…”
Section: Discussionmentioning
confidence: 77%
“…Whereas, for the learners subjected to the high mental load conditions, the enthusiastic human voice increased extraneous cognitive load while decreasing germane cognitive load. Other studies found that while human voices with positive emotional tones such as enthusiasm and happiness in a multimedia learning environment enhanced learning performance, perceived difficulty was not impacted by the voices (Lawson et al, 2021b;Liew et al, 2017Liew et al, , 2020Wang et al, 2022).…”
Section: Cognitive Load Theorymentioning
confidence: 97%
See 2 more Smart Citations
“…It was consistent with a previous study. Lawson et al (2021b) proved that positive instructors promoted the enjoyment of the lesson. This can be explained from both emotional contagion and emotional response theory.…”
Section: Discussionmentioning
confidence: 98%